Hidup Bersama dalam Perbedaan Berbasis Kearifan Lokal di Ohoidertawun dan Relevansinya bagi Masyarakat Kei - Woersok, Jolanda; Nanuru, Ricardo Freedom (Sekolah Tinggi Teologi Injili dan Kejuruan (STTIK) Kupang, 2024)
The objective of this study is to uncover the strengths of the local wisdom concept in the Ohoidertawun community, which can serve as a model for Kei society in particular and Maluku in general. This research employs a qualitative method to examine various phenomena in Ohoidertawun. The study is conducted in Ohoidertawun Village (Ohoi), Kei-Kecil District, Southeast Maluku Regency. The main reason for choosing Ohoidertawun as the research site is its harmonious social relationships despite the community's diversity in social strata and religion, which remained intact even during the Maluku conflict. The study finds that the understanding of local wisdom (Larvul Ngabal and Ain Ni Ain) remains well-preserved in Ohoidertawun, effectively influencing the community's social life. Sasi, as a form of local wisdom, plays a crucial role in managing natural resources in Ohoidertawun. Additionally, local leaders play a significant role in maintaining social cohesion within the diverse community. This local wisdom strengthens the development of economic and tourism potentials in Ohoidertawun.